Archwire Preferences and Rationale Among Iraqi Orthodontists During the Alignment Stage of Fixed Orthodontics: An Online Survey-Based Study - Dina Jawhar Butrus; Omar Fawzi Chawshli (Erbil Dental Journal, 2025)
Background: Archwire selection is critical for optimizing tooth movement and patient comfort in orthodontic treatment. However, data on archwire preferences in Iraq is limited.